Effects of equine chorionic gonadotrophin on follicular, luteal and conceptus development of non-lactating Bos indicus beef cows subjected to a progesterone plus estradiol-based timed artificial insemination protocol - Paulo Pitaluga Costa e Silva Filho; Jose N. de Souza Sales; Manoel F. de Sá Filho; Felipe Perecin; Antonio Chaves de Assis Neto; Pietro S. Baruselli; Leila Vincenti (Italian Journal of Animal Science, 2013)
The aim of this study was to evaluate the effects of equine chorionic gonadotropin (eCG) on ovarian follicular responses, corpus luteum (CL) development and conceptus length on day 16 after timed artificial insemination (TAI). A total of 124 cows at day 0 (D0) received 2 mg of estradiol benzoate (EB) and the insertion of a progesterone (P4) intravaginal device. Eight days later, the device was removed, and cows received 0.15 mg of prostaglandin and 0.5 mg of estradiol cypionate (EC), and were randomly assigned to 1 of 2 treatments: eCG (n=60), in which cows received 300 U of eCG; and control (n=64). Cows were TAI 48 h after P4 device removal. The diameter of the largest follicle (LF) present on D8 and D10 and of CL on D15 and D26 were measured. Conceptus recovered rate, conceptus length, CL diameter and weight were determined at slaughter on D26. Plasma P4 concentration was determined on D15 and D26. Follicular growth from D8 to D10 (P=0.03), the diameter of CL at D15 (P=0.03) and D26 (P=0.003) and the CL weight at day 26 (P=0.04) were greater in the eCG group than the control. However, there was no effect of eCG treatment on oestrus occurrence, conceptus recovery rate and length, or P4 concentrations on either D15 or D26. In conclusion, although eCG increases follicular responses and the diameter of the CL, this gonadotropin treatment does not influence the length of the conceptus or the P4 concentration on the subsequent oestrus cycle.